Application of Rasch Rating Scale Model to Analysis of Fear of Missing Out a Smartphone - Alizamar Alizamar (RedWhite Press, 2019)
The presence of smartphones is one of the technological advancements that have contributed greatly to changes in social behavior. This led to the inception of the Fear of Missing Out (FoMO) smartphone device. The purpose of this study therefore was to determine the right instrument to measure the FoMO smartphone by analyzing response points obtained from respondents. The study sample consisted of three groups of test subjects, from large city, small town and villages with n values of 226, 248, and 55 respectively. The data in this study were obtained using the 5-point Likert scale politomy data from a Fear of Missing out scale instrument, distributed online. The research data were analyzed using the Rasch model by testing rating scale analysis through Threshold. The results showed that the rating scale answered choices turned into a 3-point Likert scale with those not right, less right, and very right.